2017
DOI: 10.1515/ijcre-2016-0188
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Arrhenius Activation Energy and Binary Chemical Reaction on Convective Flow of a Nanofluid over Frustum of a Cone with Convective Boundary Condition

Abstract: In this article, we investigate the effects of Arrhenius activation energy with binary chemical reaction and convective boundary condition on natural convective flow over vertical frustum of a cone in a Buongiorno nanofluid under the presence of thermal radiation. The zero nanoparticle flux condition is used at the surface of frustum of a cone rather than the uniform wall condition to execute physically applicable results. For this complex flow model, a suitable non-similarity transformations are used initiall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Nanofluid past a stretching sheet along with activation energy and convective boundary conditions was analyzed by Dhlamini et al [50] who found that the concentration distribution showed a decreasing trend in the case of improvement in the reaction rate constant parameter. Chetteti and Chukka [51] manipulated the consequences of activation energy and convective boundary conditions on nanofluid flow over a cone.…”
Section: Introductionmentioning
confidence: 99%
“…Nanofluid past a stretching sheet along with activation energy and convective boundary conditions was analyzed by Dhlamini et al [50] who found that the concentration distribution showed a decreasing trend in the case of improvement in the reaction rate constant parameter. Chetteti and Chukka [51] manipulated the consequences of activation energy and convective boundary conditions on nanofluid flow over a cone.…”
Section: Introductionmentioning
confidence: 99%
“…The boundary conditions are below, (see Ali and Sandeep [42]) and The governing equations for continuity, momentum, temperature, and concentration are below and are based on the assumptions stated above (see Vajravelu and Nayfeh [40], Chetteti and Chukka [41]).…”
Section: Mathematical Formulationmentioning
confidence: 99%
“…Abhas et al 2 studied the stagnation point of a Casson fluid by considering the binary chemical reaction. Chetteti and Chukka 3 examined the activation energy effect over a vertical frustum Buongiorno nanofluid. Khan et al 4 considered a stretched surface to investigate the impact of activation energy in a binary chemical reaction of Tio 2 ‐CuO‐H 2 O nanomaterials.…”
Section: Introduction and Literature Surveymentioning
confidence: 99%